Linear and nonlinear optical properties of an off-center donor in GaAs/AlGaAs and AlGaAs/GaAs core-shell ellipsoidal quantum dots. (September 2017) - Shi, L.; Yan, Z.W.
Abstract: In the present work, the linear and nonlinear absorption coefficients and refractive index changes of an off-center donor in both GaAs/Al0.3 Ga0.7 As and Al0.3 Ga0.7 As/GaAs core-shell ellipsoidal quantum dots have been studied, emphasizing on the influence of impurity position and the shapes of core and shell. The results show that the impurity position and the shape of core and shell have an important effect on the optical properties of the system, and the influence of core and shell shapes in such two core-shell structures is different. The physical reasons for the results have been discussed in detail. Highlights: The influence of different shapes of core and shell has been considered. The influence of different positions of impurity has been considered. We have investigated both core-shell and inverted core-shell quantum dots.